Optimisation and formability study of AA5052 through incremental sheet forming. (2017) - Baruah, Angshuman; Pandivelan, C.; Jeevanantham, A.K.; Das, Subhodeep
In this paper, a well-organised and optimised methodology, Taguchi-grey relational analysis, is integrated with the experimental results of incremental sheet forming (ISF) process while considering multiple response characteristics. This tactic combines the orthogonal array design of the experiment with grey relational analysis. The main objective of this study is to attain improved formability and depth at fracture and reduced downward force. Grey relational theory is applied to explore the optimum process parameters which optimise the response characteristics. The experiment is executed using Taguchi's orthogonal L9 array (3 4 ). Each experiment is executed under diverse settings of input parameters. From the response table, the grey relational grade value for each level of experiment is duly noted. From the analysis, the best combination of forming parameters is found out. These experimental results prove that the suggested method efficiently and effectively improves the forming performance of ISF process.